The four-day work week - Grosse, Robert E. (Routledge, Taylor & Francis Group, 2018)
Presenting an appealing argument for why the four-day workweek benefits both the organization and the employee, this provocative book delves into why, explores the means for achieving it, and scrutinizes the barriers to getting there. --